Insight of Women's Sexual Function and Intimate Relationships AfterTermination of Pregnancy: A Review on Recent Findings and FuturePerspectives - Bianchi-Demicheli, Francesco; Ortigue, Stephanie (Current Women's Health Reviews, 2007)
Introduction : Controversy exists over psychological risks associated with termination of pregnancy(TOP). Although some studies recently shed some lights on the consequences of TOP on women's emotions andmental health, the positive and negative psychological and psychiatric impacts of TOP on sexual psychodynamicand intimate relationships have been poorly investigated. Objective :The objective of this article is to review the studies focusing on women's sexual function and intimaterelationships after TOP. Methods: A systematic search of the literature was performed. Studies had to have a quantitative or qualitativeevaluation of sexuality after TOP. Results: Fourteen studies were included. Sexual dysfunctions were reported in up to 30% after TOP. Womenundergoing a TOP had significantly more conflicts in their partnerships. This was similar in all studies. Separationoccurred in about one quarter of all couples. Nevertheless, long-term effects of TOP on sexual function were lessfrequent than short-term impacts. Discussion :Some studies show an increase in sexual dysfunction after TOP. Nevertheless, follow-up studies showthat persisting negative impacts of TOP on sexual function and intimate relationships are rare. In about half of thecouples separated after a TOP, TOP seemed not to have directly led to the separation. Rather, psychological factors,together with intimate relationship problems might have played a role in failed contraception. Sexual response ispsychosomatic and so often difficult to understand. A detailed exam is thus needed before and after TOP in order toestablish the importance of either its organic or psychological factors.
Keywords: libido